Aberrant Methylation of HLTF Gene in Human Esophageal Cancer. (1st March 2016) - Wang, Liang; Zhang, Xiaojing; Yin, Peng; Gao, Yan; Zhang, Yuan; Feng, Xianling; Chen, Si; Yu, Huimin; Huang, Weiling; Huang, Yong; Jian, Qianhe; Zhao, Zhenfu; et al.
Abstract: The aim of this study was to investigate whether and at which neoplastic stage promoter hypermethylation of Helicase-like Transcription Factor ( HLTF ) is involved in human esophageal carcinogenesis. The researchers examined HLTF promoter hypermethylation using real-time quantitative methylation-specific PCR in 229 primary human esophageal tissues of contrasting histological types. Both HLTF mean normalized methylation value (NMV) and hypermethylation frequency were significantly higher in dysplastic Barrett's esophagus (Dÿ 0.0303 and 10.0%), and esophageal adenocarcinomas (EAC, 0.0079 and 10.4%) than in normal esophagus (NE, 0.0006 and 0.0%; p<0.05 and p<0.05, respectively). Incremental increases in the frequency of HLTF hypermethylation were observed during progression from NE (0.0%) to Barrett's esophagus (BE, 3.3%), D (10.0%), and EAC (10.4%). Meanwhile, HLTF mean NMV was significantly higher in esophageal squamous cell carcinoma (ESCC, 0.0102) than in NE (p<0.05). Also, HLTF was hypermethylated in 7.7% ESCCs. Furthermore, mean NMV of HLTF was significantly higher in current alcohol drinking EAC patients (0.0194) than in non-current ones (0.0066, p<0.05). HLTF hypermethyaltion is an uncommon event in human esophageal cancer, but occurs early in a subset of EAC, and is related to the alcohol drinking status of EAC patients.